Herpes Zoster Masquerading as a Chemical Burn Secondary to Hair Dye. Issue 2 (March 2017) - Crowley, Timothy P.; Stevenson, Susan
Abstract : Chemical burns secondary to hair dye are very rare but have been reported. Here, we present a case of herpes zoster, which was initially mistaken for a chemical burn. Herpes zoster reactivation (shingles) is common and can give rise to skin loss clinically similar to that of a burn. It is important that clinicians consider this alternative diagnosis to ensure that timely antiviral therapy is initiated so as to reduce further skin loss and future scarring.